My first ABC (London Ladybird Books, 2015)
This fun board book introduces young children to first concepts and themes. A great introduction to the alphabet, little ones will be learn new words as they go from A to Z in this beautifully illustrated book. There is lots of opportunity to extend your child's vocabulary talking about all the colourful things they can see
Linguistic
1 2
Keywords: Board books; English language -- Alphabet -- Pictorial works -- Juvenile literature; English language -- Alphabet